Graphene, an Interesting Nanocarbon Allotrope for Biosensing Applications: Advances, Insights, and Prospects. (February 2021) - Menaa, Farid; Fatemeh, Yazdian; Vashist, Sandeep K; Iqbal, Haroon; Sharts, Olga N; Menaa, Bouzid
Graphene, a relatively new two-dimensional (2D) nanomaterial, possesses unique structure (e.g. lighter, harder, and more flexible than steel) and tunable physicochemical (e.g. electronical, optical) properties with potentially wide eco-friendly and cost-effective usage in biosensing. Furthermore, graphene-related nanomaterials (e.g. graphene oxide, doped graphene, carbon nanotubes) have inculcated tremendous interest among scientists and industrials for the development of innovative biosensing platforms, such as arrays, sequencers and other nanooptical/biophotonic sensing systems (e.g. FET, FRET, CRET, GERS). Indeed, combinatorial functionalization approaches are constantly improving the overall properties of graphene, such as its sensitivity, stability, specificity, selectivity, and response for potential bioanalytical applications. These include real-time multiplex detection, tracking, qualitative, and quantitative characterization of molecules (i.e. analytes [H2 O2, urea, nitrite, ATP or NADH]; ions [Hg 2+, Pb 2+, or Cu 2+ ]; biomolecules (DNA, iRNA, peptides, proteins, vitamins or glucose; disease biomarkers such as genetic alterations in BRCA1, p53) and cells (cancer cells, stem cells, bacteria, or viruses). However, there is still a paucity of comparative reports that critically evaluate the relative toxicity of carbon nanoallotropes in humans. This manuscript comprehensively reviews the biosensing applications of graphene and its derivatives (i.e. GO and rGO). Prospects and challenges are also introduced.